Waist circumference correlates with liver fibrosis in children with non-alcoholic steatohepatitis. Issue 9 (24th January 2008) - Manco, M; Bedogni, G; Marcellini, M; Devito, R; Ciampalini, P; Sartorelli, M R; Comparcola, D; Piemonte, F; Nobili, V
Abstract : Objective: Waist circumference is widely accepted as a risk factor for cardiovascular disease and metabolic syndrome. Non-alcoholic fatty liver disease (NAFLD) is a feature of the metabolic syndrome. A contribution of metabolic syndrome, and especially of waist circumference, to liver fibrosis in children with NAFLD is strongly suspected. Design: Cross-sectional study. Setting: Department of Hepatogastroenterology and Nutrition, Paediatric Hospital "Bambino Gesù", Rome, Italy. Patients: 197 consecutive Caucasian children with NAFLD (136 males and 61 females) aged 3–19 years. Main outcome measures: Multivariable logistic regression models were used to examine the contribution of gender, age, body mass index (BMI) and metabolic syndrome components (waist circumference, high-density lipoprotein (HDL)-cholesterol, triglycerides, blood pressure and glucose) to the odds of liver fibrosis as detected by liver biopsy. Results: 92% of the children had BMI ⩾85 th percentile and 84% had a waist ⩾90 th percentile for gender and age. Ten per cent of the children had metabolic syndrome and 67% had liver fibrosis, mostly of low degree. At multivariable analysis, waist was the only metabolic syndrome component to be associated with liver fibrosis. This was seen both when the components of the metabolic syndrome were coded as dichotomous (odds ratio (OR) = 2.40; 95% confidence interval (CI), 1.04 to 5.54) and continuous (OR = 2.07; 95% CI, 1.43 to 2.98 for a 5 cm increase). In the latter case, age was also associated with the outcome (OR = 0.70; 95% CI, 0.55 to 0.89 for a 1 year increase). Conclusions: Abdominal rather than generalised obesity contributes to liver fibrosis in children with NAFLD. Waist is also the only component of the metabolic syndrome to be associated with fibrosis in these children. Therefore, the presence of abdominal obesity is an additional criterion for the selection of children and adolescents who should undergo extensive investigation, including liver biopsy.